Safety and Health for Workers Research and Practical Perspective - Fasanya, Bankole (IntechOpen, 2020)
This book provides workers and individuals with knowledge on the effective ways to understand the importance of human health and safety in workplaces. Workplace incident scenarios and research findings on human health and safety that could be an ideal information source for university students and workers are detailed in the book. Knowledge made available includes: • Ergonomics, spine deformity associated with human posture. • Gender differences in biomechanical effects of the upper extremities. • Working conditions and gender inequalities and their effects on health and safety promotions. • Social support and job satisfaction relationship at workplaces. • Recommendations to enhance good handwashing practices. • Worker's Act impacts on health and safety practices. • Good hygiene practices at public places. Its comprehensive scope, along with its quick understanding, makes this book a handy working reference for good health and safety practices at workplaces.